Highly thermal conductive benzoxazine‐epoxy interpenetrating polymer networks containing liquid crystalline structures. Issue 24 (25th August 2017) - Liu, Ying; Chen, Jiming; Zhang, Yaoheng; Gao, Sheng; Lu, Zaijun; Xue, Qingbin
ABSTRACT: A diamine‐based benzoxazine monomer (Bz) and a liquid crystalline epoxy monomer (LCE) are synthesized, respectively. Subsequently, a benzoxazine‐epoxy interpenetrating polymer network (PBEI) containing liquid crystalline structures is obtained by sequential curing of the LCE and the Bz in the presence of imidazole. The results show that the preferential curing of LCE plays a key role in the formation mechanism of liquid crystalline phase. Due to the introduction of liquid crystalline structures, the thermal conductivity of PBEI increases with increasing content of LCE. When the content of LCE is 80 wt %, the thermal conductivity reaches 0.32 W m −1 K −1 . Additionally, the heat‐resistance of PBEI is superior to liquid crystalline epoxy resin. Among them, PBEI55 containing equal weight of Bz and LCE has better comprehensive performance. Its thermal conductivity, glass transition temperature, and the 5 % weight loss temperature are 0.28 W m −1 K −1, 160 °C, and 339 °C, respectively. By introducing boron nitride (BN) fillers into PBEI55, a composite of PBEI/BN with the highest thermal conductivity of 3.00 W m −1 K −1 is obtained. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1813–1821 Abstract : A highly thermal conductive benzoxazine‐epoxy interpenetrating polymer network (PBEI) containing liquid crystalline structures is successfully prepared by sequentially curing liquid crystalline epoxy (LCE) and benzoxazine (Bz) in the presence of imidazole.